Teor, acúmulo e eficiências nutricionais de nutrientes em porta-enxertos de caramboleira em substrato adubado com zinco - De Lima Neto, Antonio J.; Natale, William [UNESP] (Revista Brasileira de Ciencias Agrarias, 2014)
Plant species differ in their ability to absorb, translocate and utilize nutrients in their metabolism. Information about the influence of zinc with regard to nutritional efficiency in starfruit rootstocks is scarce in literature. In this direction, the study aimed to evaluate the influence of Zn on the content, accumulation, absorption efficiency, transport and use of nutrients in the starfruit rootstock. The experimental design used was randomized blocks with five doses of zinc: 0 (zero), 2, 4, 6, and 8 mg of Zn dm-3, consisting of four replications and three plants per plot. At 170 days after administering the zinc, the plants were collected, divided into shoots and roots. The plants were then dried and milled to calculate levels and rates. After which, nutrient accumulations, as well as the absorption efficiency, transport and utilization of macro and micronutrients were calculated. The zinc content in the shoots and roots of the rootstocks of starfruit increased with the increasing levels of Zn in the doses. The calcium content in the roots also increased with the increasing doses of zinc. On the other hand, the increasing doses of zinc actually decreased the levels of Mn in the shoots. The results allow to conclude that the transport of Ca and Mn from the roots to the shoots were reduced with increasing doses of zinc; zinc increased the efficiency of N, Ca, Mg, B and reduced that of Zn.
Content, accumulation and nutritional efficiencies of nutrients of the starfruit rootstocks in the substrate fertilized with zinc
Keywords: Averrhoa carambola L.; Micronutrients; Nutrient absorption